Analisis Upaya Guru Dalam Meningkatkan Hasil Belajar Bahasa Arab Siswa Kelas VII di Masa Pandemi Covid- 19 Di MTs Negeri Nagekeo Nusa Tenggara Timur - Nur Sarfian; M. Ilham Muchtar; Nasruni Nasruni (Universitas Muhammadiyah Makassar, 2021)
The aims of this study were: 1) To find out the process of learning Arabic for grade VII student at MTs Negeri Ngekeo during the Covid-19 Pandemic, 2) To find out the teacher’s efforts in improving Arabic learning outcomes for grade VII student at MTs Negeri Nagekeo during the Covid-19 Pandemic.The results of this study indicate that; In the process of learning Arabic, the role of Arabic teachers in learning Arabic at MTs Negeri Nagekeo has made efforts to improve students’ Arabic learning outcomes. in this case, there are several process of lesarning Arabic, namely: making syllabus, making lesson plans,and learning approaches. then there are several efforts made by teachers in improving Arabic learning outcomes, namely; Arabic teachers provide materials, Arabic theachers provide five vocabularies to memorize the objects in the park, then provide motivation, do learning strategies and get.